Factors Associated With Severity of Cubital Tunnel Syndrome at Presentation. (May 2023) - Zhang, Dafang; Earp, Brandon E.; Homer, Scott H.; Blazar, Philip
Background: The outcomes of cubital tunnel syndrome surgery are affected by preoperative disease severity. The aim of this study was to identify factors associated with clinical and electrodiagnostic severity of cubital tunnel syndrome at presentation. Methods: We retrospectively identified 213 patients with electrodiagnostically confirmed cubital tunnel syndrome who underwent cubital tunnel surgery from July 2008 to June 2013. Our primary response variable was clinical cubital tunnel syndrome severity assessed by the McGowan grade. Our secondary response variables were sensory nerve action potential (SNAP) recordability, presence of fibrillations, and motor nerve conduction velocities (CVs) in the abductor digiti minimi (ADM) and first dorsal interosseous (FDI). Bivariate analysis was used to screen for factors associated with disease severity; significant variables were selected for multivariable regression analysis. Results: Older age was associated with higher McGowan grade and diabetes mellitus was associated with unrecordable SNAPs on bivariate analysis. No other variables met inclusion criteria for multivariable regression analysis for McGowan grade or unrecordable SNAPs. Multivariable regression analysis showed older age and higher Distressed Communities Index (DCI) to be associated with decreased motor nerve CVs in ADM. Multivariable regression analysis showed higher body mass index (BMI) and higher DCI to be associated with decreased motor nerve CVs in FDI. No variable was associated with the presence of fibrillations. Conclusions: A subset of patients with cubital tunnel syndrome may benefit from earlier referral for hand surgery evaluation and earlier surgery. Older patients, with higher BMI, with diabetes mellitus, and with economic distress are at higher risk for presentation with more severe disease.